A novel treatment for malignant spasticity: The therapeutic use of stereotactic radiosurgery (SRS). (April 2022) - Nicosia, Luca; Rossato, Elena; Avesani, Renato; Marchioretto, Fabio; Armani, Giuseppe; Zamperini, Massimo; Foti, Giovanni; Jafari, Fatemeh; De Simone, Antonio; Ruggieri, Ruggero; Alongi, Filippo; Ferrari, Federico
Highlights: Malignant spasticity is characterized by increased muscle contraction, also painful. Drugs and surgery have sometimes complications in these frail patients. SRS to the spinal roots can be a non-invasive way to treat malignant spasticity. 3 patients treated with SRS reported a clinical benefit with no acute toxicity. Abstract: Spasticity is a clinical condition secondary to central nervous system damage, which impairs patients' mobility and quality of life. Stereotactic radiosurgery (SRS) to the spinal roots responsible of the spasms might represent a non-invasive therapy. The present are the preliminary results of the first clinical use of this novel technique.